2002
DOI: 10.2466/pms.2002.95.2.621
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of an Adolescent Version of the Barratt Impulsiveness Scale-11 for a Sample of Italian High School Students

Abstract: The purpose of this study was to extend the development of the Italian version of the Barratt Impulsiveness Scale for use with adolescents. The analyses which led to the development of this version were based on data from 563 high school students. The internal consistency was good (Cronbach alpha=.78). A confirmatory factor analysis identified six first-order factors which converged into two second-order factors, a General Impulsiveness factor and a Nonplanning Impulsiveness factor. The General Impulsiveness f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 25 publications
7
64
0
5
Order By: Relevance
“…Other studies (e.g., Fossati et al 2002;Yao et al 2007) have found support for 6-factor model as well based on samples of culturally distinct youth. However, the present study did not find support for a second-order 3-factor model identical to the one suggested by Patton et al (1995).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Other studies (e.g., Fossati et al 2002;Yao et al 2007) have found support for 6-factor model as well based on samples of culturally distinct youth. However, the present study did not find support for a second-order 3-factor model identical to the one suggested by Patton et al (1995).…”
Section: Discussionmentioning
confidence: 93%
“…During the translation and retroversion of the BIS-11 appropriate procedures (e.g., avoiding item bias or differential item functioning) were followed. The simplification procedure used by Fossati et al (2002) was used. Some items that were difficult to understand or that described situations uncommon to adolescents were reworded with some modifications (e.g., item 7.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Noteworthy, this study discussed how the instability in the factor structure across different studies could be more related to problems with the underlying construct than to methodological issues or culture infl uences (Fossati, Barratt, Acquarini, & Di Ceglie, 2002). There has been accumulating evidence that impulsivity is a multidimensional factor and its heterogeneous manifestations could infl uence the degree to which scores purely capture specifi c aspects of the construct.…”
Section: Discussionmentioning
confidence: 99%